Peningkatan Pengetahuan dan Skrining Anemia pada Remaja Putri SMP Negeri 11 Denpasar - Ida Bagus Oka Suyasa; I Gusti Ayu Dewi Sarihati; Aprilia Rakhmawati; Ni Made Sri Dwijastuti (Yayasan Literasi Sains Indonesia, 2025)
Anemia is characterized by low Hemoglobin (Hb) levels, which is a major health problem affecting adolescent girls, with a prevalence that remains relatively high. Anemia in adolescent girls is largely caused by increased iron requirements during puberty and blood loss during menstruation. Untreated anemia can continue into pregnancy and affect the health of both mother and child. This activity aimed to educate and screen 40 female students at SMP Negeri 11 Denpasar for anemia. The methods used include health education through interactive counseling, Hb level screening using photometry, the formation of adolescent health cadres and data analysis using statistical tests to determine the increase in knowledge. The screening results showed that 9 participants had symptoms of anemia with Hb <12 g/dL. The counseling session successfully increased the participant’s knowledge significantly, with the average post-test score jumping from 56 to 76 compared to the pre-test results. Although the educational intervention proved to be effective in increasing knowledge about anemia, the importance of follow-up medical treatment and continuous monitoring is very much needed. This activity successfully increased adolescent girls’ knowledge about anemia. However, follow-up in the form of iron tablets and dietary changes is required. Continuous intervention with the involvement of families and schools is expected to reduce the prevalence of anemia and improve the health quality of adolescent girls in the area.